2015
DOI: 10.14238/pi55.3.2015.153-7
|View full text |Cite
|
Sign up to set email alerts
|

Immature-to-total neutrophil ratio as an early diagnostic tool of bacterial neonatal sepsis

Abstract: Background Bacterial sepsis is the main cause of morbidity and mortality in neonates. Early diagnosis and appropriate treatment for the condition can reduce mortality rates. Blood cultures are the gold standard to diagnose bacterial sepsis, but they require 3-5 days for results, whilst the disease may progress rapidly in neonates. Examination of immature-to-total neutrophil ratio (I/T ratio) in peripheral blood smears is a quicker and less expensive method to diagnose bacterial sepsis in neonates. Some studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
2
7
0
1
Order By: Relevance
“…The sensitivity of the three examinations is quite good, I/T ratio has shown a sensitivity of 88.46%; and specificity of 81.48%, CRP has sensitivity of 88.5%, specificity of 83.3%, and PCT has sensitivity of 92.6% and specificity of 97.5%. Procalcitonin is a very specific and sensitive indicator of neonatal sepsis, which can only be examined after the baby is 3 days old or more (Darnifayanti et al, 2015;Loni et al, 2016;Memar et al, 2017). Unfortunately, all of the laboratory procedure mentioned above require high cost and not readily available in every healthcare facilities, especially in peripheral areas.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the three examinations is quite good, I/T ratio has shown a sensitivity of 88.46%; and specificity of 81.48%, CRP has sensitivity of 88.5%, specificity of 83.3%, and PCT has sensitivity of 92.6% and specificity of 97.5%. Procalcitonin is a very specific and sensitive indicator of neonatal sepsis, which can only be examined after the baby is 3 days old or more (Darnifayanti et al, 2015;Loni et al, 2016;Memar et al, 2017). Unfortunately, all of the laboratory procedure mentioned above require high cost and not readily available in every healthcare facilities, especially in peripheral areas.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, 23 subjects had positive blood cultures; IT ratio had a sensitivity of 88.46%. 16 In this study, leukopenia (10/49; 20%) was more frequent than leukocytosis (7/49; 14%). A study in Guangzhou City reported that leukopenia was found in 35% of neonatal sepsis patients compared to leukocytosis in 4% of patients.…”
Section: Discussionmentioning
confidence: 43%
“…By using a cut-off of I/T ratio > 0.15 in California, was obtained a sensitivity of 89% and a specificity of 94%. 23 I/T ratio could be used as a dignose instrument for early diagnosis of bacterial sepsis in neonates because I/T ratio had a high sensitivity and specificity. In this study, out of 59 samples, showed a sensitivity and specificity of I/T ratio manually by 69.2% ,and 83.9%, 63.9% PPV, NPV 87% 69.2% ,and 83.9%, 63.9% PPV, NPV 87% and LR of 3.06.…”
Section: Resultsmentioning
confidence: 99%